Long‐Circulating Theranostic 2D Metal‐Organic Frameworks with Concurrent O2 Self‐Supplying and GSH Depletion Characteristic for Enhanced Cancer Chemodynamic Therapy. Issue 6 (24th April 2022) - Xu, Rui; Saw, Phei Er; Xu, Lei
Abstract: Two‐dimensional (2D) nanomaterials have attracted increasing attention in cancer theranostics due to their ultrahigh specific surface area resulting in more radicals and/or reactive oxygen species (ROS) generation in chemodynamic therapy (CDT). However, their biomedical prospects are greatly limited by poor biocompatibility, low dispersion, weak stability, and the potential threat of their high immunogenicity. Moreover, rapid depletion of ROS by the high level of antioxidants (e.g., glutathione) in cancer cells severely limits the therapeutic effects of cancer CDT. Herein, a robust method is developed to improve the biomedical application of 2D nanomaterials via constructing a 2D nanomaterials delivery nanoplatform with hemoglobin‐based minerals biological coat for the safe encapsulation, long blood circulation, and controlled release of 2D nanomaterials. After intravenous administration and then internalization by cancer cells, the acidic microenvironment and high concentration of H2 O2 can trigger rapid release of Cu‐T nanoscale metal‐organic frameworks (nMOFs) from Cu‐T@MH. Then, the released Cu‐T nMOFs with simultaneous high ROS production and GSH depletion endow the Cu‐T@MH nanoplatform with enhanced cancer CDT. Besides, the fluorescence recovery of tetrakis(4‐carboxyphenyl) porphyrin in Cu‐T nMOFs during the GSH depletion process can accurately visualize the cancer therapeutic action. Abstract : Herein, a robust method is reported to construct a 2D nanomaterial delivery nanoplatform with hemoglobin‐based minerals biological coat, for safe encapsulation, and controlled release of 2D nanomaterials. By improving the biocompatibility, dispersion, and stability of 2D nanomaterials with the hemoglobin‐based coat, a long‐circulating theranostic nanoplatform with concurrent O2 self‐supplying and GSH depletion for enhanced cancer chemodynamic therapy is obtained.